Case report of a massive giant ameloblastoma and its management - Manayath, Nithya; Vanguri, Gayathri Priyabindu Vardhani; Gujjalanavar, Rajendra Suresh; Manjunath, Adarsh; Bhat, Balachandra; G., Pooja Rao (International Surgery Journal, 2022)
Ameloblastoma is a benign odontogenic tumor. It is slow growing, locally aggressive, rare tumor, accounting for 1% of all the jaw tumors. Here, we report a case of a Giant ameloblastoma in a 38-year-old gentleman who presented with a massive tumor of the mandible, possibly the largest reported in literature. The tumor had caused significant facial disfigurement and functional impairment leading to nutritional deficiency, anemia and dehydration induced elevated renal parameters. It was neglected by the patient for over ten years, due to the fear of surgery and financial constraints. Pre-operative evaluation included 3-Dimensional computerized tomographic imaging of the head and neck and optimization of deranged hematological & renal parameters and high blood pressure. Surgical treatment entailed complete tumor resection with adequate margins and microvascular reconstruction with fibular free flap in a single stage. This case of a giant multicystic ameloblastoma of the mandible, possibly the largest of its kind, was managed by complete surgical resection and a simultaneous single stage reconstruction with complete financial aid provided by our institution for the entire treatment. Finally, providing the patient, an acceptable functional, aesthetic, and oncological outcome.